Cyber-Nationalism in China. Challenging Western media portrayals of internet censorship in China - Jiang, Ying (University of Adelaide Press, 2012)
While Cyber-Nationalism in China examines fundamental questions surrounding the political implications of the Internet in China, it avoids simply predicting that the Internet does or does not lead to democratization. Applying a theoretical approach based on the Foucauldian notion of governmentality, the book builds on current scholarship that has attempted to move beyond examining the dynamics of the socio-cultural and -political use of new media technologies. Instead, this book's more intricate theoretical approach does not only accommodate the kind of liberal (apolitical or political) use observed on the Internet in China, but indicates that desires for political change, such as they are, are implicitly embedded in the relationship between China's online communities and state apparatus - noting, however, that the latter claims total governance over the Internet in the name of the people.